The RISPOSTA procedure for the collection, storage and analysis of high quality, consistent and reliable damage data in the aftermath of floods. (19th October 2015) - Ballio, F.; Molinari, D.; Minucci, G.; Mazuran, M.; Arias Munoz, C.; Menoni, S.; Atun, F.; Ardagna, D.; Berni, N.; Pandolfo, C.
Abstract: Despite the perceived abundance of information collected after a disaster, available data furnish a narrow picture of flood impacts, or they are difficult to compare so as to produce an integrated interpretation of flood events. This is due to the diversity of the purposes for which data are collected and the variety of stakeholders involved in data collection and management. The RISPOSTA procedure addresses the need for standardised ways to collect flood damage data and to create consistent and reliable flood databases that meet the objectives of risk mitigation. In this regard, the procedure satisfies several requirements of loss data: (1) the data should refer to the different exposed sectors so as to supply a comprehensive view of flood impacts; (2) they should be collected at the finest scale so that the proper scale of analysis can be chosen by subsequent data aggregation; (3) they should be linked to the physical event as well as to the features of the different exposed elements so as to supply information on both flood impacts and their explicative variables; and (4) they should be collected at different times according to the unfolding of the event in order to describe the entire range of possible damage.